2014
DOI: 10.3928/01477447-20141023-57
|View full text |Cite
|
Sign up to set email alerts
|

Drug Elution From High-Dose Antibiotic-Loaded Acrylic Cement: A Comparative, In Vitro Study

Abstract: High-dose antibiotic-loaded acrylic cement (ALAC) is used for managing peri-prosthetic joint infections (PJIs). The marked increase in resistant high-virulence bacteria is drawing the attention of physicians toward alternative antimicrobial formulations loaded into acrylic bone cement. The aim of this in vitro study was to determine the elution kinetics of 14 different high-dose ALACs. All ALAC samples showed a burst release of antibiotics in the first hour, progressively decreasing over time, and elution curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 34 publications
2
26
0
4
Order By: Relevance
“…Otherwise, desired concentrations cannot be achieved with poorly soluble antibiotics like cefepime or ampicillin. [8][9][10] Nonetheless, this method may work in the same way even if the molecule had high or low solubility. The effect might be more prominent in low solubility drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, desired concentrations cannot be achieved with poorly soluble antibiotics like cefepime or ampicillin. [8][9][10] Nonetheless, this method may work in the same way even if the molecule had high or low solubility. The effect might be more prominent in low solubility drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when higher quantities of antibiotics (2–4 g per 40 g of PMMA [42]) are placed within the articular space in the form of a bone cement spacer to treat PJI, retrieval studies have demonstrated that offending bacteria remain alive within the surrounding tissues [43]. More recent investigations have revealed the limitations of using PMMA as a method of antibiotic-delivery: antibiotics rapidly elute within the first 24 h, but logarithmically decline over a matter of days [44]; antibiotic release is limited to the outer 100 μm layer of the PMMA [45]; and that prolonged sub-therapeutic intra-articular concentrations of antibiotic can undesirably lead to the development of drug-resistant bacteria [24]. …”
Section: Contemporary Treatment Of Pji: Limited Successmentioning
confidence: 99%
“…In response to the above limitations, investigators have responded by changing the mixing process of PMMA to increase porosity and improve elution profiles [44], using binding agents to increase elution [46] and using newer antibiotics with longer half-lives in an effort to prolong their intraarticular effects [47]. More recently, good PJI treatment success rates have been reported by introducing a percutaneous catheter at the time of revision surgery and regularly infusing antibiotics into the joint space for several weeks [48].…”
Section: Contemporary Treatment Of Pji: Limited Successmentioning
confidence: 99%
“…Linezolid is generally a bacteriostatic agent with a spectrum of activity comparable with that of daptomycin. From a practical standpoint, 22,49 0.5 g 1 g Y 1.25% w/w maximum studied in vitro Fluconazole 16,52 NR 2 g N 8% w/w maximum studied in vitro Gentamicin 21,22,24,37,44 0.5-1 g 0.25-4.8 g N Imipenem-cilastatin 41,44 NR NR Y 10% w/w maximum studied in vitro Linezolid 53,54 NR NR N 15% w/w maximum studied in vitro Meropenem 17, 55 5 g NR Y 20% w/w maximum studied in vitro Micafungin 16 NR NR Y 4% w/w maximum studied in vitro Moxifloxacin 17 NR NR N 20% w/w maximum studied in vitro Piperacillin 38,44 NR 8 g Y 2.5% w/w maximum studied in vitro Piperacillin-tazobactam 22 NR 4.5 g Y Rifampin 17 NR NR Y 20% w/w maximum studied in vitro Teicoplanin 35,41,44,56 NR 3.6-10 g e Y f 10% w/w maximum studied in vitro Tigecycline 35,57 NR NR Y 10% w/w maximum studied in vitro Tobramycin 22,42,44 0.5-1. linezolid incorporates into PMMA and appears to withstand the temperatures generated during polymerization. 53,54 Linezolid is commercially available as a solution for injection, a filmcoated tablet, and flavored granules for oral suspension.…”
Section: Oxazolidinonesmentioning
confidence: 99%